Environmentally friendly AgBiS2 nanocrystal-based high-performance quantum-dot photodetectors - Kang, Jinhyeon; Oh, Jae Taek; Kim, Hyeokjun; Kim, Hanjae; Choi, Hyosung; Jung, In Hwan (Applied surface science, 2022)
[Display omitted] •Environmentally friendly Pb-free QPDs were reported by utilizing AgBiS2 NCs.•A novel CPE increased D* of QPDs by 3–4.5 times higher than that without CPE.•The ultrafast response time of 1.0 μs were achieved under 680 nm red light.•The promising D* of 1.4 × 1012 Jones at −0.5 V was achieved under 680 nm light.•The highest D* values and fastest response time were reported among the AgBiS2 QPDs. Lead-free quantum-dot photodetectors (QPDs) are currently the subject of research interest due to the environmental threat posed by lead, but relatively poor photodetection ability has been reported so far. Here, we develop high-performance AgBiS2 nanocrystal (NC)-based QPDs with a responsivity (R) of 0.55 A/W and detectivity (D*) of 1.4 × 1012 Jones at −0.5 V under a 680 nm LED light (1.0 mW/cm2) by incorporating a novel conjugated polyelectrolyte (CPE) as a cathode buffer layer (CBL) on the surface of the electron transporting layer (ETL). The CPE was developed by co-polymerization of bromohexyl-substituted fluorene and pyrene rings, followed by quaternization with trimethylamine at the terminal alkyl chains. The synthesized CPE decreased the work function and reduced the number of trap sites at the ETL surface, which increased photocurrent density and reduced dark current density, resulting in a D* value by 3 to 4.5 times greater than that without CPE treatment. Our AgBiS2 NC-based QPDs achieved ultrafast rising and falling response times of 1.0 and 3.2 μs, respectively, under the 680 nm LED light, and the CBL layer was able to rapidly remove residual current density in the off-light state, improving the dynamic characteristics of AgBiS2 QPDs under near-infrared light (940 nm).